Outcomes of delivering a fertility preservation service for women with cancer over a 12-year period at a UK assisted conception unit. (17th February 2020) - McDougall, Sophia; Vogt, Katharina S.; Wilkinson, Anna; Skull, Jonathan; Jones, Georgina L.
Abstract: This service evaluation aimed to appraise the delivery of a fertility preservation service for women with cancer which was established in 2005 as part of an Assisted Conception Unit. First, the ACU-database was interrogated between 08/2005 and 01/2017; revealing 174 women received referrals over the 12-year period with a steady referral increase each year. Demographic analyses revealed factors, such as being partnered, to be strong indicators of whether women would seek FP or not. To improve service provision, women who had consented to be contacted for audit, administrative and research purposes, received questionnaires to ascertain their perspectives on the FP decision-making process, their outcomes and ACU after-care. The majority perceived their experience as excellent due to the care they received from ACU staff, speed and efficiency in service delivery. The increasing number of referrals since 2005 is reassuring. However, this audit also highlighted shortcomings of the service, such as limited awareness of the fertility counselling service and lack of after-care. IMPACT STATEMENT: What is already known on this subject? There has been an increase in women diagnosed with cancer undergoing fertility preservation (FP) before starting potential gonadotoxic treatment. Offering FP to these women is essential as the ability to have future children is often perceived as equally as important as survivorship, and a source of hope for the future. What do the results of this study add? This study presents a service evaluation, across a 12-year period, of delivering FP services to women with cancer in one UK Assisted Conception Unit (ACU). Women's experiences of the service were evaluated to enhance service delivery and make recommendations for clinical practice. What are the implications of these findings for clinical practice and/or future research? The current service evaluation demonstrated increased rates of FP referral over a 12-year period for women with cancer. While this increasing number is reassuring and reflecting increased awareness among professionals and patients; shortcomings in the care pathway were also found: women reported limited opportunity to see fertility counsellors and desired better after care. This information may also be of benefit to other ACUs seeking to enhance and improve service provision in the care of women with cancer, contemplating fertility preservation.